Conclusions: Socio‑spatial change in Lithuania. Depopulation and increasing spatial inequalities - Ubarevičienė, Rūta (A+BE | Architecture and the Built Environment, 2018)
Almost thirty years ago, Lithuania became independent from the communist Soviet regime. This resulted in large social, economic, demographic and political changes. In addition to the substantial benefits that were brought by the restoration of independence and the ‘return to Europe’ (Kornai, 2006), major macro-level changes also resulted in extreme population decline. The geopolitical and economic position of Lithuania completely changed: from a relatively affluent and prosperous region in the Soviet Union, it became a relatively poor country on the periphery of the European Union. In parallel, from the receiver of large inflows of immigrants from other Soviet Republics, it started to lose its population due to large-scale out-migration to Western European countries. Today, Lithuania has one of the fastest shrinking populations in the world. Since the 2000s, the average annual population decline has been -1.2 percent (Statistics Lithuania, 2017). As this thesis has shown, population decline, where the main factor is out-migration, has been accompanied by changing residential patterns and increasing socio-spatial inequalities throughout the country. Until now, there has been very little academic research focusing on the processes and consequences of these socio-spatial developments in Lithuania. Moreover, the extent to which the existing literature properly captures the ongoing processes remains an open question. This thesis set out to fill the current knowledge gaps concerning the recent socio-spatial transformation processes and their consequences in Lithuania. The thesis aimed to contribute answers to the following questions: –– What are the main features and drivers of socio-spatial change in post-socialist Lithuania? –– Why, despite the growing economy and improvements in the standard of living, is Lithuania facing major challenges related to extreme population decline and increasing socio-spatial inequalities? ‘Lithuania Disappearing’, ‘Lithuania does not stop its decline’, ‘The threat of emigration’, ‘The forecast is bleak’ – such headlines have appeared on the front pages of the Lithuanian media almost daily in recent years. The focus of this thesis was not on the population decline per se, but on the social and spatial consequences that are related to this extreme decline. This thesis has highlighted some of the most problematic trends in socio-spatial development. Its main focus was on four interdependent areas of socio-spatial change: population decline, shifting residential patterns, processes of segregation and spatial inequalities. The emphasis was on the spatial dimensions of these processes. The thesis described the trajectories of the recent socio-spatial developments and examined why the scale and impact of the population change is exceptionally high in Lithuania. The thesis also showed how the Soviet-designed socio-spatial structures in Lithuania have adapted to the market economy environment. This study contributes to the existing literature by integrating the key processes of population decline, migration and segregation, which have been taking place in a rapidly changing post-socialist context. While the focus was on Lithuania, the results of this study will also be of value for other CEE countries, many of which have experienced similar trajectories of change during recent decades. The dissertation included five empirical chapters, with each chapter presenting different aspects of socio-spatial change and addressing specific research questions. Chapters 2 and 3 focused on the country as a whole. These chapters analysed the geographical patterns of population decline and the role of selective migration on population redistribution and growing socio-spatial inequalities. Chapters 4, 5 and 6 focused on areas where the socio-spatial transformations have been the most intense – the metropolitan regions and, in particular, the Vilnius metropolitan region. These chapters contribute to the limited knowledge concerning the processes of ethnic and socioeconomic segregation in Lithuania. These are also the first studies analysing how the levels of segregation have changed over time in Lithuania. The remainder of this concluding chapter is structured as follows. Firstly, the main findings of the five empirical chapters are summarised. Section 7.3 then presents an overall reflection and discussion of the research findings. In Section 7.4, the limitations of the thesis are discussed and, finally, Section 7.5 sketches some directions for further research.